Efficacy and safety of dupilumab in Japanese adults with moderate‐to‐severe atopic dermatitis: a subanalysis of three clinical trials. (28th November 2019) - Katoh, N.; Kataoka, Y.; Saeki, H.; Hide, M.; Kabashima, K.; Etoh, T.; Igarashi, A.; Imafuku, S.; Kawashima, M.; Ohtsuki, M.; Fujita, H.; Arima, K.; et al.
Summary: Background: Dupilumab, a human monoclonal antibody, blocks the shared receptor unit for interleukin‐4 and interleukin‐13. International phase II and III studies have evaluated the efficacy and safety of dupilumab in adults with moderate‐to‐severe atopic dermatitis (AD), but the effects of dupilumab in Japanese patients have not been reported. Objectives: To evaluate the efficacy and safety of dupilumab in Japanese patients with moderate‐to‐severe AD. Methods: We analysed the efficacy and safety of dupilumab in the Japanese cohorts of a 16‐week, phase IIb dose‐finding trial (AD‐1021; NCT01859988); a 16‐week, phase III, placebo‐controlled monotherapy trial (LIBERTY AD SOLO 1; NCT02277743) and a 52‐week, phase III, placebo‐controlled study of dupilumab with topical corticosteroids (LIBERTY AD CHRONOS; NCT02260986). Results: Twenty‐seven, 106 and 117 Japanese patients were enrolled in AD‐1021, SOLO 1 and CHRONOS, respectively. Baseline disease severity was numerically higher in the Japanese cohort than in the overall study population. Generally, dupilumab significantly improved signs and symptoms of AD, including pruritus and patient quality of life, compared with placebo in the Japanese cohort, consistent with the overall study population. The combined safety profile of dupilumab in the Japanese cohort was similar to that in the total study populations; dupilumab was associated with an increased incidence of injection‐site reactions and conjunctivitis compared with placebo. Dupilumab was associated with rapid reduction in thymus and activation‐regulated chemokine and gradual IgE reductions. Conclusions: Dupilumab alone or with topical corticosteroids improved signs and symptoms of AD, had an acceptable safety profile, and suppressed biomarkers of type 2 inflammation compared with placebo in Japanese adult patients with moderate‐to‐severe AD. What's already known about this topic? Differences in atopic dermatitis (AD) pathology have been reported between Asian and Western populations, in which distinct helper T‐cell activation profiles have been observed. International clinical studies in adults with moderate‐to‐severe AD have evaluated the efficacy and safety of dupilumab, which blocks interleukin‐4 and interleukin‐13, key molecules in type 2 inflammation. The effects of dupilumab in Japanese patients specifically have not yet been reported. What does this study add? Dupilumab alone or with topical corticosteroids improved signs and symptoms of AD and had an acceptable safety profile compared with placebo in Japanese patients with moderate‐to‐severe AD. The effects were comparable with those observed in the overall study population. Reported immunological differences in AD pathology in Asian patients may be secondary to type 2 immune activation. Abstract : Plain language summary available online Respond to this article